Challenges To Accelerate The Reduction Of Stunting Prevalence In The Working Area Of Anyar Community Health Center, Kosambironyok Village, Serang District, Year 2022 - Raden Renni Roostriyani; Titin Eka Sugiantini (Lembaga Pengembangan Kinerja Dosen, 2022)
Indonesia is one of the countries with a high stunting rate. In Indonesia, the strategy to accelerate the reduction of stunting is carried out by involving various figures from the government, academia, the private sector, the community, philanthropy and the mass media, and is coordinated by the Vice President. The aim of this research is to find out the implementation strategy for reducing stunting in Kosambironyok Village, Anyar District, Serang Regency in 2022. The type of research used is a qualitative method. The data sources used in this study are primary and secondary data. The informants who played a role in this study consisted of 2 groups, namely the group of informants and the group of key informants. The results of this study indicate that health workers at the Puskesmas, District officials and village officials understand their respective roles in working together to accelerate the reduction of stunting. It is hoped that all health workers will take an active role with the government in implementing the program to reduce stunting rates in toddlers. The stunting reduction program can be carried out by conducting socialization regarding the process of preventing stunting from an early age and how to overcome it.